The histone methyltransferases Trithorax and Ash1 prevent transcriptional silencing by Polycomb group proteins. - Klymenko, T.; Muller, J. (EMBO Reports, 2004)
Transcriptional on and off states of HOX genes and other developmental control genes are maintained by antagonistic regulators encoded by trithorax group (trxG) and Polycomb group (PcG) genes. The trxG proteins Ash1 and hTRX and the PcG repressor E(z) are histone methyltransferases (HMTases) that methylate distinct lysine residues in the N-terminal tail of histone H3. trxG proteins are generally thought to function as activators of HOX genes, but how histone methylation by Ash1 and Trx promotes HOX gene transcription is not clear. Here, we show that in ash1 and trx mutants expression of HOX genes is lost within their normal expression domains, but we find that, contrary to expectation, this expression is restored in ash1 and trx mutants that also lack PcG gene function. Moreover, such trxG PcG double mutants show severe misexpression of HOX genes and, hence, ectopic activation of HOX genes caused by the removal of PcG gene function also occurs in the absence of ash1 and trx function. Together, these results suggest that the Ash1 and Trx HMTases are not "coactivators" required for transcriptional activation of HOX genes, but function specifically as anti-repressors. We propose that histone methylation by Ash1 and Trx is required continuously throughout development to prevent inappropriate PcG silencing of HOX genes in cells in which they must stay transcriptionally active.